Pengaruh Media Infografis dalam Penulisan Teks Pidato Persuasif Berdasarkan Gender Kelas IX SMPIT Ibnu Khaldun - Rizqi Aji Pratama; Aghnia Syadza (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2024)
Infographic media is one of the latest learning media that can be utilized in language learning with various advantages, including: presenting important information in a simple form; having visual elements; presented in one whole picture. Previous research mentioned that infographics can increase interest and writing ability. Therefore, this study aims to observe the effect of the media on persuasive speech text writing with a one group pretest-postest research method involving 113 students in grade IX of SMPIT Ibnu Khaldun in 2023/2024. The results showed that infographics could not improve the ability to write persuasive speech texts compared to video media. The results also mentioned that there was a difference in ability between males and females in writing persuasive speech texts. However, learners felt that infographics made it easier for them to see and develop ideas for writing.